“Les Trois Sauvages”: Yvan Goll Translating T.S. Eliot in Exile - Arber, Solange (TTR, 2023)
Yvan Goll (1891-1950) adopted English as a third language during his exile in the United States between 1939 and 1947. This paper examines how the bilingual Franco-German poet became trilingual by gradually incorporating English into his work through translation. Yvan Goll’s experiences with English-language literature prior to his exile, documents concerning his language lessons in New York, and his correspondence with American poets show his need and ability to connect with the local literary scene, unlike other refugees of the older generation. Yvan Goll published several poems translated from English into French in French-language newspapers and journals. The typescript of his French translation of T.S. Eliot’s “The Dry Salvages I” offers some insight into his translation process and his strategy of positioning himself as a translator of English-language poetry.